PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS IV SDN 01 BANDAR BUAT KOTA PADANG - Viorenza, Laura; Media, Afriza; Zuryanty; Fitri, Ummiatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
IPAS learning in the Merdeka Curriculum is designed to promote meaningful, student-centered learning through discovery-based activities. However, the learning process in grade IV of SD Negeri 01 Bandar Buat, Padang City was still dominated by conventional methods, with lesson modules that were not optimally designed and low student participation, resulting in learning outcomes that did not meet the Minimum Learning Achievement Criteria. This study aimed to improve students’ learning outcomes and learning activities through the implementation of the Discovery Learning model. This research employed Classroom Action Research (CAR) conducted in two cycles involving 28 fourth-grade students. Data were collected through tests and non-test techniques, including learning outcome tests, observations of lesson modules, teacher and student activities, as well as assessments of students’ attitudes and skills. The results showed an improvement in lesson planning quality from 92.86% in Cycle I to 96.43% in Cycle II, teacher activity from 87.50% to 96.88%, and student activity from 81.25% to 96.88%, all categorized as very good. These findings indicate that the Discovery Learning model is effective in improving the quality of IPAS learning processes and learning outcomes in elementary schools.